High entropy Sr((Zr0.94Y0.06)0.2Sn0.2Ti0.2Hf0.2Mn0.2)O3−x perovskite synthesis by reactive spark plasma sintering. Issue 2 (3rd April 2019) - Biesuz, Mattia; Fu, Shuai; Dong, Jian; Jiang, Anna; Ke, Daoyao; Xu, Qiang; Zhu, Degui; Bortolotti, Mauro; Reece, Michael J.; Hu, Chunfeng; Grasso, Salvatore
ABSTRACT: A rising interest in entropy-stabilized oxides in recent years has been driven by their attractive functional properties. Their synthesis usually requires prolonged exposure at high temperature to promote solid-state diffusion without the application of pressure. In this work, we report the synthesis of a high entropy perovskite, Sr((Zr0.94 Y0.06 )0.2 Sn0.2 Ti0.2 Hf0.2 Mn0.2 )O3− x, in a relatively short time (minutes instead of hours) using a spark plasma sintering (SPS) furnace. Comparative analysis showed that conventional pressureless sintering at 1500°C for 2 h results in porous materials with large thermodynamically stable pores (tens of µm), while SPS processing produces dense materials in a single step by reactive sintering at 1475°C in 9 min. SPS is therefore an attractive route for the production, synthesis and sintering of dense high-entropy oxides.